Outcomes and imaging findings of respiratory epithelial adenomatoid hamartoma: a systematic review. Issue 6 (18th January 2019) - Safi, Chetan; Li, Carol; Tabaee, Abtin; Ramakrishna, Rohan; Riley, Charles A.
Abstract : Background: Respiratory epithelial adenomatoid hamartoma (REAH) is a recently classified histopathologic diagnosis often identified incidentally following endoscopic sinus surgery (ESS) for presumed chronic rhinosinusitis. Limited data exist defining preoperative imaging features and surgical outcomes. The purpose of this study is to examine characteristic imaging findings of REAH and postoperative olfactory and recurrence outcomes. Methods: A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines on articles published from 1995 to present. PubMed, EMBASE, and Ovid MEDLINE databases were queried for studies pertinent to imaging findings of REAH and surgical outcomes. Quality of articles was assessed using the Methodological Index for Non‐Randomized Studies (MINORS). Results: A total of 294 articles were identified, with 15 meeting inclusion criteria. Seven articles assessed both imaging findings and surgical outcomes. Three articles focused exclusively on imaging, whereas 5 examined surgical outcomes. Olfactory cleft (OC) widening greater than 10 mm on computed tomography (CT) was characteristic of REAH. A total of 441 patients with REAH were included; 221 patients (50.1%) had concurrent nasal polyposis, whereas 154 patients (34.9%) had isolated REAH. Surgical intervention ranged from simple excision to complete ESS. Sixty‐five percent (65%) of patients reported improved olfaction; 4.1% of patients recurred with follow‐up ranging from 4 months to 5 years. Conclusion: A widened OC may suggest the presence of REAH. This disease process has been identified in patients with nasal polyposis or encountered as an isolated lesion. Targeted surgery may result in improved olfaction and a low likelihood of recurrence, though long‐term prospective studies are necessary.